PENGEMBANGAN E-BOOK IPA BERBASIS FLIP PDF PROFESSIONAL UNTUK MENINGKATKAN KEMAMPUAN SCIENTIFIC EXPLANATION SISWA SMP - Ana Wardatul Jannah; Sri Wahyuni; Rusdianto Rusdianto (STKIP PGRI Situbondo, 2023)
This study aims to develop a science e-book based flip PDF professional to improve the scientific explanation ability of grade VII junior high school students at SMP Negeri 7 Jember. This research is a type of research and development. This research was conducted with the ADDIE development research model. The stages of this research procedure, are: 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data collection techniques used are test and non-test, the test consists of pre-test post-test and non-test consists of observation, interview, validation, student response, and documentation. Based on the results of the validator assessment, a validation score of 91% was obtained in the very valid category. Then the results of the practicality analysis by the observer obtained a practicality score of 83.71% with practical criteria. In addition, the effectiveness results obtained an n-gain result of 0.62 with a moderate increase category and student response obtained an average of 93.64% with an very good category. So it can be concluded that a science e-book based flip PDF professional is valid, practical, and effectively used in the learning process to improve the scientific explanation ability of junior high school students.